Predicting Work–Family Balance: A New Perspective on Person–Environment Fit - Liu, Pei; Wang, XiaoTian; Li, Aimei; Zhou, Lei (Frontiers in Psychology, 2019)
Work–family balance continues to be a burgeoning topic of organizational research, yet, while the various antecedents of work–family balance have been identified, researchers have, to date, neglected the effect of congruence versus incongruence with regard to work–family integration preferences and the corresponding supplies at work. The current research investigates whether work–family integration preferences and organizational supplies jointly affect work–family balance, and the distal family–related outcomes including marital satisfaction and family functioning, from a person–environment fit perspective. Polynomial regression analysis and response surface methodology are used to test the study’s hypotheses. Results of the polynomial regressions on 393 employees are found to support the congruence effect hypotheses. In particular, the results show that employee work–family balance is higher when work–family integration preferences and organizational supplies are congruent, as opposed to incongruent. An individual’s balance is higher when preferences and supplies are aligned at higher levels rather than at lower levels. In addition, the asymmetrical shape of the surface along the incongruence line indicated that an employee’s work–family balance tends to be damaged once organizational supplies exceed personal preferences. Moreover, through creating a block variable based on the five polynomial terms, we found that congruence/incongruence in respect of work–family integration preferences and supplies yields distal effects on both family functioning and marital satisfaction. Our findings support our hypotheses and are also in line with both person–environment fit theory and balance theory. Theoretical and practical implications for keeping work-family balance are also discussed.